Faktor-Faktor Yang Mempengaruhi Intensitas Perilaku Wajib Pajak Badan Dalam Penggunaan E-Filing Spt ( Studi Pada Kantor Pelayanan Pajak Pratama Raba Bima ) - R AYU IDA ARYANI (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2020)
The recent study intends to uncover and analyze the effect of the issues relating to utility perception, practical perception, security and confidentiality, and taxpayers’knowledgeaboutinformation technology on the intensity of corporate taxpayers’behaviors in utilizing E-Filling. The study is conducted in three regencies, such as Dompu, Bima and the city of Bima. The population of the current study are 770 corporate taxpayers which are registered in Raba Bima Primary Tax Office and have utilized e-filling. There are 89 respondents involved which are generated by using SlovinTechnique. SPSS V.20 is applied to analyze data. The findings of the current study indicate that the issues relating to utility perception, practical perception, security and confidentiality have positive and significant impact on the intensity of corporate taxpayers’ behaviors in utilizing e - filling. Meanwhile, taxpayers’ knowledge about information technology has not positive and significant influence on the intensity of corporate taxpayers’ behaviors in utilizing e-filling. The implication of the current study for Raba Bima Primary Tax Office is that the tax office should consider the issues relating to utility perception, practical perception, security and confidentiality, and taxpayers’ knowledge about information technology in order to maximize the successfulness of utilizing e -filling and be adopted by entire corporate taxpayers.